Qualitative Analysis of Implementation Constraints of Sustainable Irrigation Project in Agricultural Areas of Indonesia - Wulandari Alwinda Puspasari; I Putu Artawan (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the obstacles in implementing sustainable irrigation projects in Indonesia’s agricultural sector, considering the country’s high dependence on stable and efficient water availability. Despite the urgent need for sustainable irrigation to support agricultural productivity and food security, numerous barriers remain in practice, reducing the effectiveness of irrigation systems. This research focuses on identifying and categorizing these obstacles into technical, social, economic, and policy aspects in order to provide comprehensive insights into the challenges faced by farmers and stakeholders. Materials and methods A qualitative research approach was employed, using in-depth interviews with farmers and relevant stakeholders, focus group discussions (FGDs), and direct field observations in selected agricultural regions. The collected data were analyzed thematically to identify recurring issues and interrelated problem patterns. This methodological framework allowed the study to capture the perspectives of multiple actors and reveal systemic challenges in irrigation project implementation. Results. The findings indicate that technical constraints are primarily due to aging infrastructure, leakage in irrigation channels, and lack of routine maintenance. From the social perspective, the main issues include limited community participation and low awareness of equitable water management. Economic barriers arise from inadequate government funding and minimal community contributions for infrastructure upkeep. On the policy level, weak institutional coordination and overlapping regulations were identified as significant impediments. Conclusions. The study concludes that achieving sustainable irrigation in Indonesia requires a collaborative strategy that integrates government agencies, local communities, private sector involvement, and non-governmental organizations. A more holistic and participatory approach in planning, implementation, and evaluation processes is crucial to overcoming these obstacles. Such integrative efforts will be vital for strengthening agricultural resilience and ensuring national food security.